Etnografi Pemirsa dan Penggunaan Televisi dalam Keluarga - Triwardani, Reny (Jurnal Ilmu Komunikasi, 2012)
Abstract: This research studies the television watching activities of two families in Yogyakarta, which does not intend to measure and find out a specific effect of media usage on family informants but merely gives a description of watching television as a cultural practice. The study was also conducted as a counter-argument from the tradition of media effects research on passive audiences. This research uses ethnographic audience, and the result shows that watching behavior in the family is not monotonous and passive. They do not really give full attention to watch television. Watching television is only one of the existence cultural practices and not the only practices in their daily life.Abstrak: Di dalam kehidupan sehari-hari, manusia masa kini telah menjadi sedemikian terbiasa dengan kegiatan menonton. Penelitian ini menjelaskan pengalaman menonton yang bertujuan mengeksplorasi penggunaan media televisi dalam rutinitas keseharian keluarga informan. Penelitiaan ini menggunakan etnografi pemirsa terhadap dua keluarga informan yang tinggal di Yogyakarta. Dengan mempertimbangkan aspek-aspek yang sifatnya kontekstual, penggunaan media televisi oleh keluarga informan menunjukkan bahwa menonton televisi merupakan salah satu praktik budaya dan bukan satu-satunya dalam rutinitas keseharian. Keberbedaan pola menonton memperlihatkan juga perilaku menonton yang tidak monoton dan pasif.